(untitled) (Architecture Image Studies, 2025)
The concept of green marketing has become widely accepted in many Arab countries and many organizations have made serious steps to produce environmentally friendly goods. Also, Arab consumers are increasingly concerned about protecting the environment and purchasing eco-friendly goods. So, this research aims to determine the role of digital green marketing campaigns on consumers’ purchase intention in Saudi Arabia and Egypt. The research based on a descriptive analytical approach. The primary data was collected through the questionnaire for this study, and statistical methods were used to analyze data that was collected from the research sample. Results indicated that most of respondents in Saudi Arabia and Egypt had high awareness about concepts of green products, green marketing and digital marketing. Also, results showed that most Saudi respondents visited shopping sites more than Egyptian respondents to know green products, and these sites had a big impact on purchase intention, but Egyptian respondents visited social media more than Saudi respondents to know green products, and these sites had a big impact on purchase intention. The research recommended that Companies should invest and develop more on eco-practices to have a bigger impact on the market and emerge as environmentally conscious organizations.